2022
DOI: 10.3390/cancers14071606
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Fusobacterium nucleatum after Abdominoperineal Resection for Anal Squamous Cell Carcinoma

Abstract: Main prognostic factors of anal squamous cell carcinoma (ASCC) are tumor size, differentiation, lymph node involvement, and male gender. However, they are insufficient to predict relapses after exclusive radiotherapy (RT) or chemoradiotherapy (CRT). Fusobacterium nucleatum has been associated with poor prognosis in several digestive cancers. In this study, we assessed the association between intratumoral F. nucleatum load and clinico-pathological features, relapse, and survival in patients with ASCC who underw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…defined that mutations in PIK3CA were associated with worst OS in recurrent patients after an abdominoperineal resection. A recent study established that high levels of Fusobacterium nucleatum were associated with better OS and DFS in patients who suffered a progression and underwent abdominoperineal resection 36 . In a previous work, we identified that presenting a high or moderate impact of genetic variants in BRCA2 , ZNF750 , FAM208B , ZNF599 , and ZC3H13 genes was related to DFS in localized ASCC 12 .…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…defined that mutations in PIK3CA were associated with worst OS in recurrent patients after an abdominoperineal resection. A recent study established that high levels of Fusobacterium nucleatum were associated with better OS and DFS in patients who suffered a progression and underwent abdominoperineal resection 36 . In a previous work, we identified that presenting a high or moderate impact of genetic variants in BRCA2 , ZNF750 , FAM208B , ZNF599 , and ZC3H13 genes was related to DFS in localized ASCC 12 .…”
Section: Discussionmentioning
confidence: 73%
“…A recent study established that high levels of Fusobacterium nucleatum were associated with better OS and DFS in patients who suffered a progression and underwent abdominoperineal resection. 36 In a previous work, we identified that presenting a high or moderate impact of genetic variants in BRCA2, ZNF750, FAM208B, ZNF599, and ZC3H13 genes was related to DFS in localized ASCC. 12 This is the first study in localized ASCC that associated CNVs with DFS.…”
Section: Discussionmentioning
confidence: 84%
“…250 Similarly, for anal squamous cell carcinoma patients undergoing abdominal perineal resection after radiotherapy/chemoradiotherapy with high levels of F. nucleatum had longer overall survival and disease-free survival. 251 Thus, intratumoral microbiota can be used as biomarkers for diagnosis and prognosis to provide potential treatment guidance for patients with different risk stratifications. Until now, most research on intratumoral microbes has been based on surgically removed samples, but not all cases present the opportunity to operate.…”
Section: The Diagnostic and Prognostic Roles Of Intratumoral Microbiotamentioning
confidence: 99%
“…Nevertheless, data directly linking the microbiome with anal cancer are currently scarce. A prospective study by Elnaggar et al [27 ▪ ] described changes in beta diversity composition in patients with localized anal squamous cell carcinoma (ASCC) An association was found between a higher intratumoral load of Fusobacterium nucleatum and survival outcomes in patients undergoing surgery for ASCC, suggesting an immune modulatory effect linked to the tumor cell lineage [28].…”
Section: Links Between the Microbiome Composition And Functions And A...mentioning
confidence: 99%
“…The connection between the microbiome and HPV has recently become a focal point of scientific research. Numerous studies have attempted to decipher the impact of the microbiome on HPV infection, persistence, and progression to cervical dysplasia and cancer in women (Table 1) [6,7,10,16,[18][19][20][21][22][25][26][27][28][29][30][31][32].…”
Section: Microbiome Composition and Human Pappilomavirus Infection Ce...mentioning
confidence: 99%